2021
DOI: 10.1080/19424280.2021.1878287
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of running wearable measurement system accuracy and reliability: can we make running shoe prescription objective?

Abstract: 1 run*.mp. (191128) 2 running.mp. or *Running/ (65348) 3 1 or 2 (191128) 4 insole.mp. (838) 5 IMU.mp. (870) 6 Wearable Electronic Devices/ or wearable.mp. (10889) 7 4 or 5 or 6 (12343) 8 kinetic.mp. or Kinetics/ (575422) 9 kinematic.mp. or *Biomechanical Phenomena/ (24482) 10 Accelerometry/ or acceler*.mp. (259557) 11 8 or 9 or 10 (842654) 12 3 and 7 and 11 (180)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
2
3
0
Order By: Relevance
“…A systematic review from Ancillao et al [ 93 ] found sensors that allow direct measurements of GRF—such as insoles, wearable load cells, or ad hoc designed pressure sensing devices—to be more reliable than GRF predicted from IMU data. This is confirmed in a recent review by Blazey et al [ 87 ] who found instrumented insoles, in particular the Loadsol system, to offer a good in-field assessment tool. However, it is important to note that when sensors are worn under the foot, they compromise the foot–ground interaction, and the loads measured do not reflect the pressure absorbed by the tissue but rather the pressure on the device or the shoe to insole interface [ 87 , 93 ].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…A systematic review from Ancillao et al [ 93 ] found sensors that allow direct measurements of GRF—such as insoles, wearable load cells, or ad hoc designed pressure sensing devices—to be more reliable than GRF predicted from IMU data. This is confirmed in a recent review by Blazey et al [ 87 ] who found instrumented insoles, in particular the Loadsol system, to offer a good in-field assessment tool. However, it is important to note that when sensors are worn under the foot, they compromise the foot–ground interaction, and the loads measured do not reflect the pressure absorbed by the tissue but rather the pressure on the device or the shoe to insole interface [ 87 , 93 ].…”
Section: Discussionsupporting
confidence: 57%
“…This is confirmed in a recent review by Blazey et al [ 87 ] who found instrumented insoles, in particular the Loadsol system, to offer a good in-field assessment tool. However, it is important to note that when sensors are worn under the foot, they compromise the foot–ground interaction, and the loads measured do not reflect the pressure absorbed by the tissue but rather the pressure on the device or the shoe to insole interface [ 87 , 93 ]. It is further emphasized that even if there is a correlation between predicted and directly measured GRF, it is difficult to estimate the absolute value of the peak force.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Measurements are sent with a frequency of up to 200 Hz, over a Bluetooth connection, to the user's smartphone. These insoles are used to study walking and running gaits in real-world settings [41,42]. In the ALAMEDA pilot studies, the insoles can readily provide accurate measurements related to gait metrics, such as step number, cadence, step cycle time, loading rate, factor of imbalance (disproportionate loading of one foot compared to the other), or peak push force.…”
Section: Smart Insolesmentioning
confidence: 99%